Indonesia - India: Shared Ancient Cultural Ties and Modern Geopolitical Values - Abdul Allam Amrullah (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
The article highlights the presence of Indic culture in Indonesia which binds the people into a common identity. Indic culture made a pervasive impact to all over the region of Southeast Asia and particularly in Indonesia. The article also touches upon the responses and diplomacy of Indian government through the course of time in order to forge more cherished and stronger relationship by invigorating soft power. Keywords: Indonesia, India, Ancient, modern, Cultural, Geopolitical Values